Microencapsulación de nutrientes aplicados alimentos - Meneses Ruiz, Lourdes del Pilar (2022)
Microencapsulation is definet as a technology of packaging solids, liquids or gases. The microcapsules can release their contents sealed at controlled rates under specific conditions, and can protect the encapsulated product of light and oxygen. Microencapsulation is formed by a micro-porous polymeric membrane of an active substance container. The material or mixture of encapsulating materials can be coated or entrapped within another material or system. A microcapsule consist of a semi-permeable membrane, spherical, thin and strong center around a solid / liquid. The materials used for micro encapsulation can be gelatin, fats, oils, arabic gum, calcium alginate, waxes, wheat, starch, corn, rice, potato, nylon, cyclodextrin, maltodextrin, sodium caseinate, whey protein or soy protein. Microencapsulation applications are aimed at textile industry, metallurgical, chemical, food, cosmetics, pharmaceuticals and medicine. Among the techniques used for microencapsulation are spray drying, drying, chilling, freeze drying, coacervation and extrusion. The substances that can be microencapsulated are vitamins, minerals, dyes, prebiotics, probiotics, flavors, nutraceuticals, antioxidants, odors, oils, enzymes, bacteria, perfumes, drugs and even fertilizers.